21st Century chemistry teacher: Analysis of TPACK of pre-service chemistry teachers in teachers college - Friska Juliana Purba; Kelly Sinaga; Debora Sitinjak; Candra Y Tahya (Pascasarjana Universitas Negeri Medan, 2023)
This research is aimed to analyze chemistry pre-service teachers' profile of the TPACK (Technology Pedagogy and Content Knowledge) competencies in Teachers College. The method used in this study was a mixed method using TPACK’s questionnaire and interview. This study revealed that Content Knowledge (CK), Technology Knowledge (TK), Pedagogy Knowledge (PK), Pedagogy Content Knowledge (PCK), and Technology Pedagogy Knowledge (TPK) components of TPACK of pre-service teachers are excellent. The Technology Content Knowledge (TCK) component needs to be improved throughout training courses that enabled the pre-service teacher to utilize, design, and apply various chemistry-based computer applications. The component of TPACK will continue to develop with the support of institutions and teaching experience. Strengthening the components of TPACK is important for a chemistry teacher to embrace 21st century learning.Keywords: Chemistry pre-sevice teacher; 21st century learning; TPACK